SINTESIS DAN APLIKASI LAPIS TIPIS TiO2 NANOTUBE UNTUK SEL SURYA - , EVANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The film of nanotube TiO2 on glass substrate for dye sensitized solar cells (DSSC) was synthesized by templating method using ZnO nanorod film as the template employing liquid phase deposition (LPD) and sol-gel method. The research aims at getting vertically alligned nanotube TiO2 film and studying the effect of the morphology on the solar cell performance. Well aligned ZnO nanorods were firstly prepared by hydrothermal method. SEM and TEM images showed that the resulted ZnO nanorod was ordered and uniform. The diameter and length of the nanorods were 100 nm and 1.5 Âµm, respectively. The XRD results showed that ZnO nanorods were wurtzite-structured ZnO with preferential orientation along (002) plane. In the fabrication process of TiO2 nanotube arrays by LPD, the synthesized ZnO nanorod films were immersed in aqueous solution consisting of TiO2 P25 and H3BO3 at room temperature for 2 h. It was found that TiO2 thin film resulted from LPD method has particulates morphology. The XRD pattern shows predominantly anatase phase with average crystallite size of approximately 39.5 nm. For sol-gel method, TiO2 sol was deposited on ZnO nanorod by dip coating with a withdrawing speed of about 2 cm/min. Titanium tetraisopropoxide (TTIP) was used as the titanium precursors. Ordered TiO2 nanotube was obtained at dip-coating cycle of 3 with anatase crystalline phase of about 600 nm long and 100 nm in diameter. Sensitization study was carried out by comparing the electronic spectra of mangosteen extract dye solution to TiO2-dye system in visible region. The solar cell characteristic was studied by analyzing its I-V curve. It is found that DSSC based on TiO2 resulted from sol-gel method has higher efficiency than those of TiO2 resulted from LPD method. The resultant DSSC has photogenerated current (Jsc) and voltage (Voc) as high as 440 Î¼A/cm2 and 470 mV, respectively with the fill factor (FF) of 0.280 and global efficiency (Î·) of 0.057%.